Self‐Adaptive Surface with Tunable Superamphiphobicity Fabricated by Femtosecond Laser Induced Backward Transfer - Kongyu Lou; Jing Qian; Xiaohan Yu; Zhaoyuan Xia; Danyang Shen; Guande Wang; Quan‐Zhong Zhao (Advanced Materials Interfaces, 2022)
Abstract In recent years, a rapid advance in fabricating smart surfaces with tunable wettability have been witnessed. However, switchable superamphiphobic surface remains a great challenge today. Here, glass surfaces with tunable wetting performance between amphipathicity and amphiphobicity, “lotus effect” and “petal effect,” isotropic and anisotropic amphiphobicity are obtained by femtosecond‐laser‐induced backward transfer (LIBT) method. By printing simple patterns, polytetrafluoroethylene (PTFE) is spatial‐selectively transferred with composite micro/nano‐structures formed on the glass surfaces, ensuring a strong repellence for water and oil. Besides, the surface topography and chemistry can be finely regulated in a single‐step process without damage to the glass, which provides the feasibility of controlling the surface wettability. Herein, applications such as high precision mixing reactor, droplet volume screening micro‐device, auto‐filtering droplet channel are designed and demonstrated. Compared to other methods, the LIBT method featuring rapid, large‐area, maskless prototyping is proved to be a promising method for programmable manipulations of functional surfaces with diverse wettability.